Clonal diversity and antifungal susceptibility of Candida spp. recovered from cow milk - Hizlisoy, Harun (Array, 2020)
The aim of this study was the isolation, identification, phylogenetic analysis and antifungal susceptibility of Candida spp. from milk samples of healthy and mastitic cows in Kayseri/Turkey. Milk samples from 300 cows were found to be negative/positive for mastitis with the California Mastitis Test. Candida spp. was isolated by using the Brillance Candida Agar Base. Phenotypic tests, Matrix Assisted Laser Desorption Ionization - Time of Flight (MALDI-TOF), and VITEK-2 analyses were applied to confirm the obtained isolates. Resistance to flucytosine, fluconazole and caspofungin antifungals of the isolates were determined by Etest and VITEK-2. The genetic homologies of Candida spp. isolates were determined by Repetitive Extragenic Palindromic-PCR (RepPCR). In this study 62 (from 53 healthy, 9 mastitic) yeast isolates were obtained and 37 (59.6 %) were identified as non-albicans Candida (NAC) species. Phenotypic tests revealed that out of 62 isolates, 29 (46.7 %), 4 (6.5 %), 3 (4.8 %), 1 (1.6 %) and, 24 (38.7 %) were identified as Candida lusitaniae, Candida catenulate, Candida tropicalis, Candida silvicola and other yeast species, respectively. Only one sample (1.6 %) was identified as Candida albicans by MALDI-TOF however, according to VITEK-2, the agent was not confirmed as C. albicans. According to antifungal susceptibility testing by VITEK-2, one (2.7 %) of the isolates was resistant to fluconazole, one (2.7 %) was resistant to caspofungin, and 4 (10.8 %) were resistant to flucytosine. However, using E test, 10 isolates (27 %) were resistant to flucytosine. Using Rep-PCR, eight genotypic clones were observed. Genotype F (13.8 %) and G (13.8 %; 2 subtypes) were common clones in this study. In conclusion, NAC species were detected in healthy and mastitic cow milk samples. Epidemiological studies need to be conducted to track effectively the main source and to understand the diversity and distribution of the agent. It is necessary to consider the potential ris